2011
DOI: 10.1186/1471-2407-11-338
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of hypoxia-inducible factor-1α P3155 also modulates PI3K pathway and inhibits growth of prostate cancer cells

Abstract: BackgroundHypoxia-inducible factor-1 (HIF-1) is a master regulator of the transcriptional response to hypoxia. It is essential for angiogenesis and is associated with tumor progression and overexpression of HIF-1α has been demonstrated in many common human cancers. Therefore, HIF-1α is one of the most compelling anticancer targets.MethodsTo identify HIF-1α inhibitors, luciferase reporter gene assay under hypoxia and normoxia was used. Detailed studies such as western blotting, RT-PCR, immunofluorescence were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
(29 reference statements)
1
11
0
1
Order By: Relevance
“…Under hypoxic condition, enhanced expression of HIF-1α in high tumorigenic cancer stem/progenitor cells sustained the activation PI3K/Akt (60,61). A recent study suggests that the PI3K/Akt signaling mediates the regulation and activation of HIF-1α (43,45).…”
Section: Discussionmentioning
confidence: 98%
“…Under hypoxic condition, enhanced expression of HIF-1α in high tumorigenic cancer stem/progenitor cells sustained the activation PI3K/Akt (60,61). A recent study suggests that the PI3K/Akt signaling mediates the regulation and activation of HIF-1α (43,45).…”
Section: Discussionmentioning
confidence: 98%
“…HIF-1 proteins are regulators of transcriptional responses against hypoxia and equally important in angiogenesis and tumor growth. An HIF-1 α inhibitor has been described to inhibit the PI3K/AKT pathway in PCa cell lines [115]. Another example is Gambogic Acid, which limits PCa development through inhibition of both PI3K/AKT and NF- κ B pathways [116].…”
Section: The Pi3k/akt Pathway In Prostate Cancermentioning
confidence: 99%
“…59 Interestingly, Manohar et al identified and tested the efficacy of a novel HIF-1α inhibitor P31555 in PCA cells, and concluded that P3155 also inhibits hypoxia-induced HIF-1α expression through inhibiting the PI3K/Akt/mTOR pathway. 60 Yan et al reported that Akt and its downstream signaling is activated in hepatocellular carcinoma cells (HCC) and controls the hypoxia-induced EMT in these cells. 55 Importantly, Akt is also activated in PCA cells under chronic hypoxic conditions and plays an important role in the hormone-refractory progression of the disease.…”
Section: Hypoxia-induced Signaling Pathwaysmentioning
confidence: 99%